Historical and Legal Features for the Development of Legal (Law) Education in 30-40s of the XX Century - N. A. Bondar (Bulletin of Kharkiv National University of Internal Affairs)
Historical and legal features for the development of legal (law) education in the pre-war period on the territory of modern Ukraine, as well as the state of regulatory provision of the educational process in higher educational institutions have been studied. The genesis of Ukrainian legal education has been analyzed and the state of training of legal personnel for state authorities has been characterized. Some features of the University education system and unification policy of the Soviet government have been highlighted. The disadvantages and advantages of the development of legal education in the studied period have been outlined.